Microbial biomass nitrogen in cerrado soil with nitrogen fertilizer application - Coser, Thais Rodrigues; Ramos, Maria Lucrécia Gerosa; Amabile, Renato Fernando; Júnior, Walter Quadros Ribeiro (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effect of different nitrogen doses and soil depths on soil microbial biomass nitrogen (NSMB) in a sandy textured Oxisol, cultivated with barley. The experiment was established in June, 2004, in an area which had been cultivated with millet for three years and subsequently with soya beans for two seasons. The treatments were four doses of nitrogen (30, 60, 90 e 120 kg ha-1) and a control without any dose. Soil samples were collected in four depths: 0–5, 5–10, 10–20 e 20–30 cm, comprising three replicates and three sampling periods: tillering, flowering and right after the harvest. The NSMB and NSMB:Ntotal decreased according to depth. Higher doses of nitrogen did not increase the NSMB. The Ntotal was not altered with the application of nitrogen, but it decreased with depth. There were negative correlations between the NSMB and soil pH for all the doses, except for the treatment without nitrogen. There were also positive correlations between the NSMB:Ntotal and NSMB, but not between NSMB:Ntotal and Ntotal.